PEMODELAN MATEMATIKA UNTUK JAM AIR JENIS POLYVASCULAR CLEPSYDRA DENGAN KASUS VISCOSITY DOMINATED - Dewi, Linda Maria E.; widowati, widowati (MATEMATIKA, 2008)
The principle_work of polyvascular clepsydra water clocks is to make the constant flow on the last vessel. A viscosity dominated case can influence a liquid flow in this clepsydra, beside the number of the vessel which build this clepsydra, will influence a constant flow duration. The increasing the number of the vessel will increase the duration of the constant flow. A case study at PT Tirta Sidatama Â is given toverify the principle_work of this clepsydra. Â